Advances in Irish Quaternary studies - Coxon, Peter; McCarron, Stephen; Mitchell, Fraser (Atlantis Press, 2017)
This book provides a new synthesis of the published research on the Quaternary of Ireland. It reviews a number of significant advances in the last three decades on the understanding of the pattern and chronology of the Irish Quaternary glacial, interglacial, floristic and occupation records. Those utilising the latest technology have enabled significant advances in geochronology using accelerated mass spectrometry, cosmogenic nuclide extraction and optically stimulated luminescence amongst others. This has been commensurate with high-resolution geomorphological mapping of the Irish land surface and continental shelf using a wide range of remote sensing techniques including MBES and LIDAR. Thus the time is ideal for a state of the art publication, which provides a series of authoritative reviews of the Irish Quaternary incorporating these most recent advances.
Keywords: Geology, Stratigraphic -- Quaternary.; Geology -- Ireland.; Ireland.; From 2 million years ago; elektronické knihy; electronic books